Sexually transmitted infections and HIV in the era of antiretroviral treatment and prevention: the biologic basis for epidemiologic synergy - Cohen, Myron S; Council, Olivia D; Chen, Jane S (Journal of the International AIDS Society, 2019)
Introduction HIV is a unique sexually transmitted infection (STI) that is greatly affected by other concomitant “classical” bacterial and viral STIs that cause genital ulcers and/or mucosal inflammation. STIs also serve as a marker for risky sexual behaviours. STIs increase infectiousness of people living with HIV by increasing the viral concentration in the genital tract, and by increasing the potential for HIV acquisition in people at risk for HIV. In addition, some STIs can increase blood HIV concentration and promote progression of disease. This review is designed to investigate the complex relationship between HIV and classical STIs. Discussion Treatment of STIs with appropriate antibiotics reduces HIV in blood, semen and female genital secretions. However, community‐based trials could not reliably reduce the spread of HIV by mass treatment of STIs. Introduction of antiretroviral agents for the treatment and prevention of HIV has led to renewed interest in the complex relationship between STIs and HIV. Antiretroviral treatment (ART) reduces the infectiousness of HIV and virtually eliminates the transmission of HIV in spite of concomitant or acquired STIs. However, while ART interrupts HIV transmission, it does not stop intermittent shedding of HIV in genital secretions. Such shedding of HIV is increased by STIs, although the viral copies are not likely replication competent or infectious. Pre‐exposure prophylaxis (PrEP) of HIV with the combination of tenofovir disoproxil fumarate and emtricitabine (TDF/FTC) prevents HIV acquisition in spite of concomitant STIs. Conclusions STIs remain pandemic, and the availability of ART may have led to an increase in STIs, as fear of HIV has diminished. Classical STIs present a huge worldwide health burden that cannot be separated from HIV, and they deserve far more attention than they currently receive.